Eficacia del tratamiento para erradicación de Helicobacter Pylori, esquema doble vs. Esquema triple aplicado a pacientes que acuden a la Clínica de especialidades Mogrovejo. - Espinoza Jumbo, Karin Jeanette (2017)
Helicobacter pylori is found in half of the worldwide population. If the infection produced by this bactery is not treated on time, it could become really severe, starting with a simple gastrointestinal problem and develop in a severe peptic ulcer, gastric adernocarcinoma or associated lymphoid gastric tissue therefore, the use of the correct medicine to contrarest the infection, has to be adapted to each patient and their medical history. For that reason there was an investigation and comparative study called “ THE EFFECTIVENESS OF THE DOUBLE TREATMENT VS TRIPLE TREATMENT, IN THE ERRADICATION OF Helicobacter Pylory, APPLIED TO THE THE CLINICA DE ESPECIALIDADES MOGROVEJO PATIENTS”. The purpose of the clinical investigation was to identify the effectivity of the double and triple treatments to erradicate the Helicobacter Pylory. To determine the erradication of the H. Pylory after the treatment and finally the comparative analisys of the Double Treatment and Triple Treatment for the erradication of the bactery. The clinical study was descriptive,tranversal and retrospective, the clininical history of 86 patients of all age groups that were infected by H.Pylory was used. The conclusive results were that the patients that received the Double Treatment, could obtain the eradication of H. Pylory in 77.5% (n=38) of 49 patients and for the Triple Treatment, the patients achieved the same result in 83.78% (n=31) 0f 37 patients. It is conclusive thtat the Triple Treatment is more succsessful, although the Double Treatment could also be used for its high percentage of possitive efficacy against H. Pylori. Important Words: Helicobacter pylori, double treatlment, triple treatment